Uncomplicated and Complicated Acute Appendicitis Induce Different Cytokine Patterns - Han, Tatu; Borman, Tuomas; Vanhatalo, Sanja; Lahti, Leo; Löyttyniemi, Eliisa; Hurme, Saija; Munukka, Eveliina; Kallonen, Teemu; Hakanen, Antti; Hollmén, Maija; Salminen, Paulina (John Wiley & Sons, 2026)
Although acute appendicitis is one of the most common reasons for emergency surgery, the immunopathogenesis of appendicitis is unclear. The aim of this prospective pre-defined subgroup analysis study was to characterize serum cytokine profiles and their diagnostic potential in distinguishing between appendicitis severity to offer further insight into the immunopathology of appendicitis. We analyzed 48 cytokines from the serum samples of patients with either uncomplicated or complicated appendicitis. Out of the 113 patients included in the study, 72 patients presented with uncomplicated and 41 patients with complicated acute appendicitis. Compared to uncomplicated appendicitis, complicated appendicitis showed statistically significantly elevated levels in interleukin 6 (IL-6) (p < 0.001), hepatocyte growth factor (HGF) (p = 0.003), and monocyte chemoattractant protein 1 (MCP-1) (p < 0.001). IL-6 had the best performance (area under curve 0.785) in predicting complicated acute appendicitis. The immune response is notably different between complicated and uncomplicated appendicitis, underlining the two different diseases within acute appendicitis. IL-6 may be utilized as a diagnostic biomarker for complicated appendicitis.